GEOPOLITICAL CONFRONTATION IN CENTRAL ASIA IN THE MID-19TH CENTURY: ANALYSIS OF THE POSITIONS OF IRAN, CHINA, AND OTHER REGIONAL POWERS - Askarov, Azimjon (Oriental Journal of History, Politics and Law, 2025)
This paper analyzes the geopolitical developments in Central Asia during the mid-19th century from the perspective of regional powers such as Iran, China, and others. Unlike traditional studies that emphasize the British-Russian rivalry, this research highlights the role of Iran’s religious-political influence and China’s economic and diplomatic actions. It also discusses the strategic importance of Afghanistan and the Emirate of Bukhara, based on primary historical documents.